Group key establishment (GKE): Two/three party key exchange to GKE - Vivek S.S.; Deva Selvi S.S.; Shukla D.; Rangan C.P. (My University, 2025)
This work presents the first scalable, efficient and generic compilers to construct group key exchange (GKE) protocols from two/three party key exchange (2-KE/3-KE) protocols. We propose three different compilers where the first one is a 2-KE to GKE compiler (2-TGKE) for tree topology, the second one is also for tree topology but from 3-KE to GKE (3-TGKE) and the third one is a compiler that constructs a GKE from 3-KE for circular topology. Our compilers 2-TGKE and 3-TGKE are first of their kind and are efficient due to the underlying tree topology. For the circular topology, we design a compiler called 3-CGKE. By extending the compilers 2-TGKE and 3-TGKE using the techniques in [?], scalable compilers for tree based authenticated group key exchange protocols (2-TAGKE/3-TAGKE), that are secure against active adversaries can be constructed. As an added advantage our compilers can be used in a setting where there is asymmetric distribution of computing power and hence applicable for low power devices such as PDA's, palmtops, sensor network nodes and mobile phones. © 2012 IEEE.